Answer:
![y = (1)/(2)e^x -(1)/(2) e^(2-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ac0dd915p0t7ecez46ral5gg6b0au0hbfr.png)
Explanation:
Given
![y=c_1e^x +c_2e^{-x](https://img.qammunity.org/2022/formulas/mathematics/high-school/8wsp22itx0f0z4dfdcx32vb3nftb75y73h.png)
![y(1) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/iwv2j13v39aqteut0y3m1l2971zs38xesf.png)
![y'(1) =e](https://img.qammunity.org/2022/formulas/mathematics/high-school/knd8pr2gbgqwduaiwzl7o6vf2amff78mce.png)
Required
The solution
Differentiate
![y' = c_1e^x - c_2e^(-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5ecf5h1igjmmkxbh8q20wfc50uc65qvtpi.png)
Next, we solve for c1 and c2
implies that; x = 1 and y = 0
So, we have:
![0 = c_1 * e^1 + c_2 * e^(-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/z6tjom21if76lmjhx3tldb2cee3g7icm0u.png)
--- (1)
implies that: x = 1 and y' = e
So, we have:
![y' = c_1e^x - c_2e^(-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5ecf5h1igjmmkxbh8q20wfc50uc65qvtpi.png)
![e = c_1 * e^1 - c_2 * e^(-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/vsim6kx9zwmwmjul6lyurnkymq9rdy7ycf.png)
--- (2)
Add (1) and (2)
![0 + e = c_1e + c_1e + (1)/(e)c_2 - (1)/(e)c_2](https://img.qammunity.org/2022/formulas/mathematics/high-school/7bv56rfh07n39wkag6b8fp06ys6q8xcmz9.png)
![e = 2c_1e](https://img.qammunity.org/2022/formulas/mathematics/high-school/exph8jtbv3ux705zk5blpqjb4tb4gmkase.png)
Divide both sided by e
![1 = 2c_1](https://img.qammunity.org/2022/formulas/mathematics/high-school/7l5nxxqwqg4vx3p1jiyzklkdt3rwjiysi6.png)
Divide both sides by 2
![c_1 = (1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/44p0cdnn4b2q931pz2ny1z0xsb83lr73ne.png)
Substitute
in
![0 = c_1 e + (1)/(e)c_2](https://img.qammunity.org/2022/formulas/mathematics/high-school/863r9dqrv7671t4wzs4uop1brkvz3h91hu.png)
![0 = (1)/(2) e+ (1)/(e)c_2](https://img.qammunity.org/2022/formulas/mathematics/high-school/b2qxiwm0ggyht5jgv8ixgckb40loquqkjl.png)
Rewrite as:
![(1)/(e)c_2 = -(1)/(2) e](https://img.qammunity.org/2022/formulas/mathematics/high-school/xrc7lkapmifo9r5th94kubtfmy3qadqkf9.png)
Multiply both sides by e
![c_2 = -(1)/(2) e^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/tveuxom2xg520v1nn2h04v6p18br7jo976.png)
So, we have:
![y=c_1e^x +c_2e^{-x](https://img.qammunity.org/2022/formulas/mathematics/high-school/8wsp22itx0f0z4dfdcx32vb3nftb75y73h.png)
![y = (1)/(2)e^x -(1)/(2) e^2 * e^(-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/uvqt5z9u9fhkmt6wueoc1k114f038w1gtw.png)
![y = (1)/(2)e^x -(1)/(2) e^(2-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ac0dd915p0t7ecez46ral5gg6b0au0hbfr.png)